I am assuming the equation is as follows
[tex]f(x) = x^2 + 3x - 10[/tex]
Since the constant 10 is -10 this tells us we are going to have different signs + - after you have factored the equation.
First thing first. Think of two numbers that will give you the product(The answer after two numbers are multiplied) of -10 and the sum(Two numbers added together) of +3. I get the 3 from the 3x.
We know 5 x -2 = -10 and the sum 5 + -2 = +3
With that said, we found our two factors
(x + 5)(x - 2)
Now write them as zeros and solve for x
x + 5 = 0
x = -5
x - 2 = 0
x = 2
So the zeros are -5 and 2.